Mobile times and temporalities: Histories of geomediation of time. (November 2022) - Özkul, Didem; Humphreys, Lee
The mobile ontology of locative media and ubiquity of location-aware technologies have led to an explicit focus on "where" and an implicit focus on "when" in geomedia studies. While welcoming this focus, we argue that this spatial bias has led the temporal dimensions of geomedia to be overlooked. Despite the growing interest that draws academic attention to mediation of time and temporal dimensions of media and data practices, there is still limited discussion on time and temporality of geomedia. We aim to fill this gap and open a debate about the temporality of geomedia based on seven oral history interviews that we conducted with mobile media scholars who pioneered in research in mobile phones from late 1990s onwards. These historical accounts include the narratives of how mobile phones were used for time-keeping, synchronizing, presencing, and coordinating everyday life. Hence, this article grounds mediation of time in the histories of geomedia.